Biosecurity Challenges: How Defense Strategies Against Tuberculosis In Asean Countries - Akhmad Sultoni Yahya; Anak Agung Banyu Perwita; Agung Risdhianto; Hikmat Zakky Al Mubaroq (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This comprehensive research provides a thorough analysis of tuberculosis (TB) incidence trends and sanitation challenges within the ASEAN region spanning from 2005 to 2021. It underscores the critical need for robust defense strategies against TB, particularly in light of setbacks exacerbated by the COVID-19 pandemic. The research, conducted in Jakarta, Indonesia, from June to July 2023, delved into biosecurity challenges of tuberculosis in ASEAN countries, using a quantitative approach and cross-sectional design. Data from 2005 to 2021, sourced from the ASEAN database, underwent descriptive statistics and trend analysis to explore TB incidence rates, ensuring a comprehensive investigation scope. The study places emphasis on the imperative of implementing comprehensive measures encompassing prevention, screening, swift diagnosis, utilization of advanced treatment regimens, and ensuring robust patient support systems. Moreover, it highlights the pivotal role of addressing sanitation challenges, as substandard conditions significantly heighten the risks of TB transmission. The study's scope encompasses an array of critical subjects, with a central focus on TB incidence rates, as well as the crucial aspects of access to improved sanitation facilities and sanitation services. The conclusion is the ASEAN region, especially the Philippines, faces a notable tuberculosis burden, coupled with uneven access to sanitation. Effective interventions and collaboration are vital for improving public health and sanitation standards in ASEAN countries.